Decreased sputum caveolin-1 is associated with systemic sclerosis related lung disease - (:unkn) unknown (My University, 2014)
AIM: To determine serum and sputum Caveolin-1 (Cav-1) levels and their associations with transforming growth factor- ß (TGF-ß) and interstitial lung disease (ILD) in systemic sclerosis (SSc). METHODS: Serum and induced sputum samples from 55 patients with SSc, 25 asthma patients and 16 healthy volunteers (HC) were tested for Cav-1 and TGF-ß by the ELISA technique. As a possible downstream signaling regulator of TGF-ß, Endothelin-1 (ET-1), a potent profibrotic protein, was also measured in all serum and sputum samples and relations with Cav-1 and TGF-ß were sought. All scleroderma patients were evaluated for their clinical and laboratory parameters. Pulmonary function tests (PFT) and high resolution computerized tomography (HRCT) were performed for the diagnosis of ILD. The alveolitis-fibrosis index and the SSc disease severity scores were noted for each patient. RESULTS: Serum Cav-1 levels were lower in SSc compared to HC (p<0.01). Cav-1 levels were significantly lower in the sputum of SSc patients compared to both control groups (p<0.001). It was also found significantly lower in SSc-ILD compared to those without ILD (0.19±0.04 vs 0.25±0.07, respectively, p<0.01). Although no difference was found in the serum TGF-ß levels among the groups, sputum TGF-ß levels correlated positively with the alveolitis index (r=0.34) and correlated inversely with FVC measurements (r=-0.44, p<0.05) among SSc patients. Serum ET-1 was significantly higher in SSc patients (p<0.01) but no association was found between ET-1 and Cav-1 or TGF-ß. CONCLUSION: These results suggest that decreased sputum Cav-1 levels is associated with SSc related-ILD and may be used as a marker for the detection of SSc-ILD.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Male; Case-Control Studies; Prospective Studies; Transforming Growth Factor beta; Lung Diseases, Interstitial; Scleroderma, Systemic; Sputum; Endothelin-1; Caveolin 1